2014
DOI: 10.3997/1873-0604.2015009
|View full text |Cite
|
Sign up to set email alerts
|

Non‐destructive assessment of hot mix asphalt compaction/density with a step‐frequency radar: case study on a newly paved road

Abstract: A Step Frequency Radar (SFR) is used for assessing the compaction of Hot Mix Asphalt (HMA) layers. The system is composed of a network analyser and an Ultra Wide Band (UWB) antenna placed above the road surface. The measurements are carried out on a new-paved road in Cagny (Normandie, France). The SFR system provides the permittivity of the first overlay. The data is corrected from vehicle vibrations and calibrated at fixed locations. Then, the HMA compaction is deduced with a Lichteneker-Rother (LR) model. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 7 publications
1
14
0
Order By: Relevance
“…A previous study carried out on 11 different rocks has reported the good repeatability of this method (Fauchard et al . ). Indeed, the permittivity of each tested rocks was averaged on 10 to 15 cores for one single type of rock at six frequencies.…”
Section: Rock Permittivity Measurementsmentioning
confidence: 97%
See 4 more Smart Citations
“…A previous study carried out on 11 different rocks has reported the good repeatability of this method (Fauchard et al . ). Indeed, the permittivity of each tested rocks was averaged on 10 to 15 cores for one single type of rock at six frequencies.…”
Section: Rock Permittivity Measurementsmentioning
confidence: 97%
“…This study updates some results of a previous work (Fauchard et al . ) and intends to test dielectric mixture models selected in the literature. To evaluate the HMA density with radar methods, rocks extracted from various quarries for road manufacturing have been studied.…”
Section: Rock Permittivity Measurementsmentioning
confidence: 99%
See 3 more Smart Citations